Large-Scale Affirmative Action in School Choice: Admissions to IITs in India - Aygün, Orhan; Turhan, Bertan (American Economic Review, 2017)
We provide a real-life application of a large scale affirmative action policy in school choice in the context of engineering school admissions in India where students not only care about what program they are matched to but also what type of seat category they are admitted under. We explain the market and the mechanism currently in use. Two significant shortcomings of the current mechanism are explained. The affirmative action policy in use leaves many seats vacant even though there are students who would take these seats. We provide the insight of a potential matching-theoretical solution to these problems.